Estimation of The Economic Costs of Deforestation in Indonesia, 2011-2013 - Robhati, Husyroniatur; Kusumawardani, Deni (Jurnal Ilmu Ekonomi Terapan, 2016)
This study is aimed to estimate economic value of deforestation in Indonesia and contribution for forestry sub-sector of GDP in Indonesia from 2011 to 2013. This study has two main variables, economic value of deforestation and EDP. Technique used to estimate deforestation economic value is benefit transfer with Total Economic Value approach. The estimation results show that real cost of deforestation in Indonesia since 2011 to 2013 increase almost four times, or about Rp 1,5 trillion to Rp 5,6 trillion. Indonesia real value EDP in 2011 is Rp 51,8 billion, increases 1,58 percent in 2012 to Rp 52,6 billion, and decrease 0,53 percent to Rp 52,3 billion in years 2013. The contribution of deforestation for forestry subsector GDP is below one percent, but in nominal term, the deforestation always has an increased value.